SUSTAINABLE STRATEGIES IN NAVIGATING OPERATIONS FOR A RESILIENT FUTURE (2025)
This book presents sustainable strategies across various operational sectors to build a resilient and efficient future. It offers a multidisciplinary approach, featuring empirical studies and case analyses from higher education, logistics, Industry 4.0 production, agriculture, and sustainable palm oil development in Malaysia. Each chapter highlights challenges and best practices in implementing sustainability principles, including green campus initiatives, e-commerce logistics service quality, natural resource management, and strategic packaging optimization. The book is designed for researchers, students, industry professionals, and policymakers seeking to understand and apply sustainable operational strategies aligned with global demands. It serves as a practical guide to integrating sustainability into diverse organizational practices for long-term impact.